Estimating the Returns to Schooling Using Cohort-Level Maternal Education as an Instrument - John V. Winters (Institute for the Study of Labor (IZA), 2014)
Formal education is widely thought to be a major determinant of individual earnings. This paper uses the American Community Survey to examine the effect of formal schooling on worker wages. Given the potential endogeneity of education decisions, I instrument for individual schooling using cohort-level mean maternal years of schooling from previous decennial censuses. The instrumental variables results suggest that schooling has a significant positive effect on worker wages. Specifically, an additional year or schooling is estimated to increase hourly wages by 10 percent for men and 12.6 percent for women.
Keywords: J24; J31; 330; human capital; education; returns to schooling; wages; maternal education